PENGARUH KUALITAS PELAYANAN DAN FASILITAS PERPUSTAKAAN TERHADAP MINAT BACA MAHASISWA PADA STIE BENTARA PERSADA BATAM - Josepin Harianja,; Feliks Dabur,; Pilifus Junianto, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
The research was conducted to determine the quality of service and facilities that affect the reading interest of students of STIE Bentara Persada Batam. Established population and samples are all students at 2020-2021 academic year, with a population of 70 respondents. The data was analyzed using SPSS 22. The results of this study suggest that the quality of service and facilities have a positive and significant impact on the interest of students. Value of service quality 0.012 is smaller than α = 0.05. Significance value of facilities 0.00 smaller than α = 0.05. Together the quality of service and facilities affect positive and significant interest in reading of students of STIE Bentara Persada Batam. The decision is based on a degree of F of 149.252 with a degree of significance 0.00 smaller than α = 0.05. Regression equations have been determined that the two free variables have a harmonious relationship with the variabel are bound. It means that when these free variables are enhanced, a student's interest in reading will increase.